POTENSI EKSTRAK DAUN Chromolaena odorata (L.) DAN Piper betle (L.) SEBAGAI HERBISIDA ORGANIK TERHADAP PENGHAMBATAN PERKECAMBAHAN DAN PERTUMBUHAN Mikania micrantha - Kiki Anggriani; Siti Fatonah; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The alternative way of environmentaly friendly weed controlling is to use Chromolaenaodorata and Piper betle extract that contain allelopathic compound and potential asorganic herbicides. The purpose of this research was to know the influence ofChromolaena odorata and Piper betle extracts in inhibiting the germination and growthof Mikania micrantha and to determine the best concentration of extracts in weedcontrolling. This research used Randomize Complete Design. The collected data wasanalyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple RangeTest if the result is significantly different. The experiment results showed that thegermination and growth of Mikania micrantha weed were reduced because of thetreatment using Chromolaena odorata and Piper betle extract. The most efficientextract concentration in controlling weed was 10% of Chromolaena odorata extract.